2021
DOI: 10.1039/d0ja00264j
|View full text |Cite
|
Sign up to set email alerts
|

Three calibration techniques combined with sample-effective design of experiment based on Latin hypercube sampling for direct detection of lanthanides in REE-rich ores using TXRF and WDXRF

Abstract: This study concerns the simultaneous detection of five rare-earth elements (REEs) – Ce, La, Nd, Pr, Sm – in ores and nodules using two X-ray fluorescence techniques (XRF): total reflection...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Latin hypercube sampling (LHS), first proposed by McKay et al , 50 is superior to all abovementioned DoEs as it can be constructed with low correlation for a large number of factors 51 and a tunable number of levels. In our resent study, 52 the DoE based on LHS (20 levels and 5 factors) with an extremely low correlation (<0.03) enabled the construction of robust PLS-R and principal component regression (PCR) calibration models using artificial mixtures of REE compounds (Fe and Ti oxides as a matrix) that outperformed univariate models providing up to several times better accuracy of Ce, La, Nd, Pr and Sm determination in REE-rich ores and ferromanganese nodules by TXRF and WDXRF.…”
Section: Introductionmentioning
confidence: 74%
“…Latin hypercube sampling (LHS), first proposed by McKay et al , 50 is superior to all abovementioned DoEs as it can be constructed with low correlation for a large number of factors 51 and a tunable number of levels. In our resent study, 52 the DoE based on LHS (20 levels and 5 factors) with an extremely low correlation (<0.03) enabled the construction of robust PLS-R and principal component regression (PCR) calibration models using artificial mixtures of REE compounds (Fe and Ti oxides as a matrix) that outperformed univariate models providing up to several times better accuracy of Ce, La, Nd, Pr and Sm determination in REE-rich ores and ferromanganese nodules by TXRF and WDXRF.…”
Section: Introductionmentioning
confidence: 74%
“…TXRF can be applied for direct analysis of iron, manganese, ferromanganese, nickel-copper sulfide ores, oceanic and lacustrine nodules [Pashkova et al, 2020;Akhmetzhanov et al, 2021;Chubarov et al, 2021]. The suspension preparation (5 mL of 1 % Triton X-100 solution and 20 mg of fine powder with a size <10 μm and internal standard of Ga) gives a possibility for fast reliable determination of major and minor elements by the internal standard method with the recovery values 75-125 %.…”
Section: Application Of Txrf To Geological Objectsmentioning
confidence: 99%
“…For instance, the differences between the TXRF results and the certified values in CRMs may be more than 30 % for As, Pb, V, Cr, Ba in the nodules due to PbLα/AsKα, BaLα/TiKα, CrKα/VKβ, VKα/TiKβ lines overlapping [Pashkova et al, 2020;Chubarov et al, 2021]. Chemometric approaches may be used to solve this problem [Akhmetzhanov et al, 2021]. It was shown that the calibration models based on partial least squares and principal component regressions provide a quantitative determination of Ce, La, and Nd content in ores and nodules using the TXRF method.…”
Section: Application Of Txrf To Geological Objectsmentioning
confidence: 99%
“…In a related study, similar improvements were obtained 57 by wet milling a clay CRM to reduce particle sizes even further (to 1–2 μm). Akhmetzhanov et al 58 compared multi- and univariate calibration for both TXRF and WDXRF analyses for the determination of REE in ores with the aim of assessing whether the cost-efficient suspension-assisted TXRF procedure could be used as an alternative to the WDXRF procedure which employed pressed pellets. A set of calibration samples with variable concentrations of REE was used to improve the accuracy.…”
Section: Grazing X-ray Techniques Including Txrf Spectrometrymentioning
confidence: 99%